2022
DOI: 10.1002/ptr.7656
|View full text |Cite
|
Sign up to set email alerts
|

Effect of curcumin on regulatory B cells in chronic colitis mice involving TLR/MyD88 signaling pathway

Abstract: Curcumin (Cur) is a natural active phenolic compound extracted from the root of Curcuma Longa L. It has anti‐inflammatory, anti‐tumor and other pharmacological activities, and is commonly used to treat ulcerative colitis (UC). However, it is not clear whether curcumin regulates the function and differentiation of Breg cells to treat UC. In this study, mice with chronic colitis were induced by dextran sulfate sodium (DSS), and treated with curcumin for 12 days. Curcumin effectively improved the body weight, col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…TNF-α, IL-6, TLR4, IL-17, NF-kB, TRIF, and IFN-γ are all important inflammatory factors and have some clinical significance for the diagnosis of UC (Du & Ha, 2020). Related studies have showed that disturbance of the internal environment (such as disturbed gut microbiota) can induce the increased expression of TLR4 on epithelial cells, endothelial cells and other membranes in intestinal mucosa, and combine with MyD88 to form TLR-MyD88 complex, so as to activate related signaling kinases, leading to the activation of transcription factor NF-κB, releasing NF-κB and translocating to the nucleus (Huang et al, 2023). When the number of NF-κB entering the nucleus increases, NF-κB entering the nucleus binds to DNA, thereby initiating a series of gene transcription, enhancing transcription, and promoting more inflammatory factors (such as TNF-α, IL-6, IL-17, TRIF, IFN-γ and so on), and then the phenomenon of chemokine secretion and macrophage infiltration occurs, ultimately forming a "cytokine storm" effect, aggravating the inflammatory response, mediating intestinal damage (such as ulcers, necrosis and), even causing carcinogenesis because of long-term accumulation (Xue et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α, IL-6, TLR4, IL-17, NF-kB, TRIF, and IFN-γ are all important inflammatory factors and have some clinical significance for the diagnosis of UC (Du & Ha, 2020). Related studies have showed that disturbance of the internal environment (such as disturbed gut microbiota) can induce the increased expression of TLR4 on epithelial cells, endothelial cells and other membranes in intestinal mucosa, and combine with MyD88 to form TLR-MyD88 complex, so as to activate related signaling kinases, leading to the activation of transcription factor NF-κB, releasing NF-κB and translocating to the nucleus (Huang et al, 2023). When the number of NF-κB entering the nucleus increases, NF-κB entering the nucleus binds to DNA, thereby initiating a series of gene transcription, enhancing transcription, and promoting more inflammatory factors (such as TNF-α, IL-6, IL-17, TRIF, IFN-γ and so on), and then the phenomenon of chemokine secretion and macrophage infiltration occurs, ultimately forming a "cytokine storm" effect, aggravating the inflammatory response, mediating intestinal damage (such as ulcers, necrosis and), even causing carcinogenesis because of long-term accumulation (Xue et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin is the main effective ingredient of Curcuma longa L. in the treatment of UC [ 111 ]. It mainly exerts its therapeutic effect on UC by regulating signaling pathways, such as TLR/MyD88, MAPK, and PI3K/AKT, and inhibiting pro-inflammatory cytokines, such as IL-1β, TNF-α, IL-33, CCL-2, IL-6, and TGF-β1 [ 112 ]. Curcumin has been found to increase the killing power of pathogenic gram-positive and gram-negative bacteria while promoting the production of short-chain fatty acids to protect the intestinal mucosa and reduce the proliferation of bacteria responsible for intestinal inflammation.…”
Section: Tcm Ingredients For the Uc Treatmentmentioning
confidence: 99%